“Disclosing the innermost part”: Exploring therapists’ constructions of shame using a story completion method - Drini, Eugenia; Kent, Tom; Frith, Hannah (European Journal for Qualitative Research in Psychotherapy, 2023)
Previous research on shame has indicated that it is an important phenomenon that can benefit or hinder the therapeutic process, depending on how it is understood and managed by therapists. However, therapists’ conceptualisations of shame have not been explored adequately. This study utilised a novel method of data collection called story-completion to examine how therapists talk about shame, and the impact this can have on how they manage it. Forty-five therapists were asked to complete a story-stem describing a therapist working with a client’s shame via an online survey platform. Foucauldian discourse analysis (FDA) was used to critically analyse participants’ stories. Shame was constructed as a rather problematic emotion that hinders the therapeutic progress by preventing the clients from revealing their “true” self. In these narratives, the therapist’s task was to uncover what is hidden behind shame. Some participants constructed the therapist as an expert, holding the appropriate knowledge to manage it. A counter position was the therapist conceptualised as humane, where they were de-skilled and vulnerable in relation to shame. We invite practitioners to be mindful of the ways that their understanding of emotions, and their role in relation to them, can impact the direction of therapy.